A Survey on Implementing Role-play as Teaching Activities for Preschools Children in Learning English During Circle Time - Abas, Aslinda; Mohd Kosnin, Azlina; Rustam Mohd Rameli, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
Role-play has been proven as one of the best activities in learning English to achieve children’s development in the areas of social and emotional, language, and cognitive. Circle time by implementing role-play in learning English for preschool children has been explored by researchers in this study, as the aim was to determine how far the preschool teachers implemented role-play as teaching activities in learning English during circle time. The survey used the qualitative approach whereby five preschool teachers in Johor Bahru were interviewed to collect data. A thematic approach was used to analyze the data. As a result, some activities enhancing children in learning English during circle time and several challenges in implementing role play for improving English during circle time were identified. This survey found that preschool teachers agreed that role play is an interesting activity but not to implement due to few challenges, as has been explained by participants.